Policy Bureaucracy: Government with a cast of thousands - Edward C Page, Bill Jenkins (Oxford University Press, 2005)
Policy bureaucracies are not simply subordinate organizations that merely do as they are told by their political masters. They cannot be, as the main part of their work is to create solutions to problems; if politicians knew how they wanted the problems solved sufficiently to give their administrative subordinates direct instructions, they would not need policy bureaucracies. Politicians are often not even generally aware that such policy problems exist before their policy officials raise them. To work on the assumption that policymaking starts off with the top brass—ministers, permanent secretaries, and the like—setting out the broad direction, and all that is left to those below them is to fill in the details in a routine or mechanical way is plain wrong. It is not wrong because such officials ‘act above their pay grade’ in the words of Alastair Campbell, the Prime Minister’s Head of Communications at the time of the Hutton Inquiry in Autumn 2003,1 implying that officials may seek to have greater influence than their position suggests they should have. They may sometimes be presumptuous in this way. Yet it is not the point of this book to find and describe examples of officials having such folie de grandeur, and we must admit to not finding any particularly clear cases where they did. We might have expected to find such instances, and should have been disappointed that we did not, if we had paid too much attention to much of the recent theoretical literature on bureaucracy that seeks to understand the motivations of politivi cians and bureaucrats by assuming an inherent power conflict between them (Huber and Shipan 2002; see Goodsell 2004 for a critical view). Officials are acting within their pay grade when they are involved in shaping policy. Indeed, doing ‘policy work’ is a conventional term used by officials in the UK to describe a certain range of jobs that middle-ranking as well as senior officials do. We simply do not know what middle-ranking officials do when they are acting within their pay grade. How such middleranking officials in policy bureaucracies are involved in policymaking as part of their everyday jobs is the central question of this book.